2009
DOI: 10.2166/wh.2009.233
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and metal water quality in rain catchments compared with traditional drinking water sources in the East Sepik Province, Papua New Guinea

Abstract: In Papua New Guinea, a significant portion of morbidity and mortality is attributed to water-borne diseases. To reduce incidence of disease, communities and non-governmental organizations have installed rain catchments to provide drinking water of improved quality. However, little work has been done to determine whether these rain catchments provide drinking water of better quality than traditional drinking water sources, and if morbidity is decreased in villages with rain catchments. The specific aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…These analysis methods for dealing with data below and above the detection limit are well documented in the literature. 27,[39][40][41][42][43][44][45][46] Tests were not performed to confirm E. coli or fecal streptococci. Thus, concentrations and reductions reported in this paper should be viewed as those of presumptive E. coli and fecal streptococci.…”
Section: Methodsmentioning
confidence: 99%
“…These analysis methods for dealing with data below and above the detection limit are well documented in the literature. 27,[39][40][41][42][43][44][45][46] Tests were not performed to confirm E. coli or fecal streptococci. Thus, concentrations and reductions reported in this paper should be viewed as those of presumptive E. coli and fecal streptococci.…”
Section: Methodsmentioning
confidence: 99%
“…The impacts documented ranged from catastrophic loss of whole villages, through destruction of water and sanitation infrastructure, to changes in source water quantity and/or quality (Mosley et al 2004;White et al 2007;Keim 2010). Studies have examined aquifer contamination from storm surge in atoll communities (Keim 2010; and changes in water quality across rainwater tanks, wells and streams (Terry et al 2001;Horak et al 2010). …”
Section: Emergency Wash and Intervention Strategiesmentioning
confidence: 99%
“…Mourits and Kumar (1995), in the context of rainwater harvesting in Fiji, showed the importance of understanding the cultural setting with respect to supporting individual actions (like establishing household water harvesting schemes), as resources are often shared at the village level. Such cultural issues and the need to understand social structures prior to intervention were cited by many authors as reasons for project failure (see also (Kuruppu 2009;Greenwell et al 2013; Guerrier et al Several studies reported assessments of water quality and contamination across multiple water source types (Mourits & Kumar 1995;Beatty et al 2004;Horak et al 2010;Psutka et al 2013). This is relevant in the context of global WaSH surveys that assess the primary water source of each household, despite the growing evidence that many households use a variety of sources for different uses (MacDonald et al 2016).…”
Section: Emergency Wash and Intervention Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this solution appears attractive from an ecological point of view, it is necessary to measure the quality of harvested rainwater due to the potential for health risks as a result of chemical and microbiological contaminants. Over the last decades, studies in numerous countries including USA, Nigeria, New-Zealand, India, Zambia, Brazil, Canada, Australia, Jordan, New Guinea and South Korea, have investigated the quality of harvested rainwater (Crabtree et al 1996;Uba and Aghogho 2000;Simmons et al 2001;Kulshrestha et al 2003;Handia 2005;May and Prado 2006;Al-Khashman 2009;Despins et al 2009;Evans et al 2009;Horak et al 2010;Lee et al 2010). In Europe, rainwater quality assessment was studied by Förster 1999;Albrechtsen 2002;Polkowska et al 2002;Fewtrell and Kay 2007;Melidis et al 2007;Oesterholt et al 2007;Sazakli et al 2007;Schriewer et al 2008;Tsakovski et al 2010.…”
Section: Introductionmentioning
confidence: 99%